Calculation of Organic Substrate Decomposition in Biofilm and Bioreactor-Filter Taking into Account its Limitation and Inhibition - Poliakov, Vadim (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2021)
The mathematical problem of the steady-state biofiltration of an organic substrate is formulated at two levels taking into account the limitation and inhibition of the rate of its decomposition. The exact and approximate solutions to the problem of substrate biooxidation in a representative biofilm were obtained and compared using test examples. Based on them an analysis of the technological process in the porous biofilter medium and the output characteristics was carried out.